The Effect Of Acid Strength Of Bronsted Acid Site On The Ability Of The Catalyst To Break The Carbon Chain Bonds Of 1-Octadekenes Into Alkanes And Short Chain Alkenes As A Substitute For Fossil Fuels - Donatus Setyawan Purwo Handoko; Triyono Triyono (Testing Center for Oil and Gas LEMIGAS, 2023)
Research has been carried out on the strength of acids on their ability to break carbon chain bonds. The preparation of the zeolite catalyst includes soaking the zeolite in distilled water for 24 hours, followed by calcination and oxidation, then followed by reduction. Further acid treatment with 6 M HCl. Then followed by washing with H2O until neutral pH (pH = 7), then dried in an oven with a temperature of 105 oC, then after becoming a zeolite catalyst used in the cracking reaction of 1-octadekenes into alkanes and short chain alkenes.The results obtained are as follows for the type of zeolite catalyst with code Z having a very low acidity level of 3.15 mmol NH3/mgZeolite, then the zeolite has been modified by a calcination process for 24 hours given the code ZCA which shows a moderate acidity level of 5, 76 mmol NH3/mg Zeolite, then the catalyst with the code ZCAO is zeolite which has been calcified and oxidized and shows a yield of 9.54 mmol NH3/mg Zeolite. Catalytic hydrocracking of 1-octadecene with ZCAO catalyst at a variation of the hydrogen flow rate of 20 mL/minute and a temperature of 450 oC resulted in alkanes and alkenes < C12 which was 15.29% maximum, followed by a hydrogen flow rate of 10 mL/minute at temperatures of 500 and 400 oC.Â